M1-like TAMs are required for the efficacy of PD-L1/PD-1 blockades in gastric cancer - Zhao, Rui; Wan, Qianyi; Wang, Yong; Wu, Yutao; Xiao, Shuomeng; Li, Qiqi; Shen, Xiaoding; Zhuang, Wen; Zhou, Yong; Xia, Lin; Song, Yinghan; Chen, Yi; et al. (Oncoimmunology, 2021)
The efficacy of PD-1/PD-L1 blockades is heterogeneous in different molecular subtypes of gastric cancer (GC). In this study, we analyzed relevant clinical trials to identify the molecular subtypes associated with the efficacy of PD-1/PD-L1 blockades, and public datasets, patient samples, and GC cell lines were used for investigating potential mechanisms. We found that GC with EBV-positive, MSI-H/dMMR, TMB-H or PIK3CA mutant subtype had enhanced efficacy of PD-L1/PD-1 blockades. Also, differentially expressed genes of these molecular subtypes shared the same gene signature and functional annotations related to immunity. Meanwhile, CIBERSORT identified that the overlapping landscapes of tumor-infiltrating immune cells in the four molecular subtypes were mainly M1-like macrophages (M1). The relationships between M1 and clinical characteristics, M1, and gene signatures associated with PD-1/PD-L1 blockades also revealed that M1 was associated with improved prognosis and required for the efficacy of PD-L1/PD-1 blockades in GC. We identified that tumor-infiltrating CD68 + CD163 − macrophages could represent M1 calculated by CIBERSORT in clinical application, and CXCL9, 10, 11/CXCR3 axis was involved in the mechanism of CD68 + CD163 − macrophages in the enhanced efficacy of PD-L1/PD-1 blockades. In conclusion, CD68 + CD163 − macrophages are required for the efficacy of PD-L1/PD-1 blockades and expand the applicable candidates in GC patients without the molecular subtypes.